The Influence of Electronic Word of Mouth (eWOM) in Enhancing the Program Registration Applicants of a Youth Organization - Susiana Nur Safitri; Sultan Sultan (AIBPM Publisher, 2024)
The study explores the impact of electronic word-of-mouth (e-WOM) on the decision-making process of registering for the AIESEC 2021 program. Conducted using a quantitative survey method, the research applies marketing communication theory to understand the influence of e-WOM on consumer behavior. Surveying 75 registrants from the UPN